Maqasidi Analysis in the Fatwa of the Indonesian Ulema Council on the Replacement of Friday Prayers with Dzuhur During the Pandemic - Aziz, Muhammad Abdul (Unisia, 2021)
The Covid-19 Pandemic limitations affected religion and soul in the community. This included prayer decisions such as, a Muslim observing the Friday prayer in a red zone during the pandemic chose religion, while one who conducts Dzuhur chose the soul. Therefore, this study used the analytical-descriptive method to explain the maqasid al-shari’ah perspective in the Indonesian Ulema Council (MUI) fatwas on the permissibility of replacing Friday prayers with Dzuhur during the pandemic. The results showed that this replacement contradicted the maqasid-masalih concept which views them as inseparable entities. It was against the comprehensiveness (shumuliyyah) principle as the main characteristic of maqasid al-shariah. This is because they lacked elasticity (murunah) which is religion main goal (al-daruriyyat al-khams). The issued MUI fatwas followed the maqasid al-shariah as comprehensive, dynamic, and elastic.